PENGARUH ONLINE CONSUMER REVIEW, SOCIAL MEDIA ADVERTISEMENT, DAN INFLUENCER ENDORSEMENT TERHADAP ONLINE PURCHASE INTENTION PRODUK AZARINE DI KOTA BANDUNG - Mardotillah, Aini Restu; Ariyanti, Maya (LPPM STIE Muhammadiah Bandung, 2023)
One strategy so that companies can compete in the era of globalization is to utilize information technology through internet media. When shopping online, consumers are very interested in beauty and care products. Several factors influence online purchase intentions, including online consumer reviews, social media advertising and influencer support. The research objective was to measure the impact of online consumer reviews, social media advertising, and influencer endorsements on online purchase intention of Azarine products in Bandung City. This study uses a quantitative approach and uses a sample of 130 respondents. Data was collected through an online questionnaire via the Google form. As a data analysis method, Partial Least Squares Structural Equation Modeling (PLS-SEM) is used. The findings are that online consumer reviews, social media advertising, and influencer support have a significant effect on the intention to buy Azarine products online.